Scaling Up Sweetpotato Through Agriculture and Nutrition in Malawi (SUSTAIN) - Remington, T. (International Potato Center, 2015)
This flyer outlines the progress made towards achieving the objectives of the SUSTAIN project in Mozambique from June 2014 to July 2015. SUSTAIN is a 5-year partnership (2013-2018), coordinated by CIP and financed by the UK Department for International Development, to scale up the nutrition benefits of biofortified orange-fleshed sweetpotato (OFSP). The goal is to reach 1.2 million households with under-5 year old children in Kenya, Malawi, Mozambique, and Rwanda.